Studi Komparasi Hasil Ujian Mahasiswa Tahun Pertama Perkuliahan Pada Mata Kuliah Autoimun - Hartanto, Deddy (BRILIANT: Jurnal Riset dan Konseptual, 2024)
The first year of college has an influence on students taking courses in the following year. The low average final exam score of students in virtual face-to-face learning was the impetus for conducting this research. A total of 40 students from the Medical Education study program were given virtual and face-to-face learning for half a semester each. A total of 10 questions with the same weight are given in the mid-term and final exams to be worked on for 50 minutes. The results of the research show that face-to-face learning causes an increase in the minimum student exam score of 14 points (28%) while the maximum score increases by two points (2.12%), the average increase is 14.41% from 71.1 to 81.35 and the standard deviation fell 12.4% from 9.03497 to 7.91477. A sigma value of less than 0.05 indicates that face-to-face learning is better than virtual face-to-face learning. Interview results support that face-to-face learning is better than virtual face-to-face learning in autoimmune courses in the Medical Education study program in the first year of study.